2015
DOI: 10.1177/0003489415573074
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Hearing and Vestibular Profiles in the Patients with COCH Mutations

Abstract: Targeted exon resequencing of selected genes using NGS successfully identified mutations in the relatively rare deafness gene, COCH, in the Japanese population. The phenotype is compatible with that described in previous reports. Additional supporting evidence concerning progressive hearing loss and deterioration of vestibular function was obtained from our study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 40 publications
2
24
0
Order By: Relevance
“…These frequencies are relatively high and are compatible with those from past reports. It is worthy of note that these mutations ( WFS1 : c.2507A>C (p.K836T), COCH : c.1115T>C (p.I372T)) are recurrent mutations in Japanese patients[27, 28]. Therefore, they may be related to a founder effect.…”
Section: Discussionmentioning
confidence: 99%
“…These frequencies are relatively high and are compatible with those from past reports. It is worthy of note that these mutations ( WFS1 : c.2507A>C (p.K836T), COCH : c.1115T>C (p.I372T)) are recurrent mutations in Japanese patients[27, 28]. Therefore, they may be related to a founder effect.…”
Section: Discussionmentioning
confidence: 99%
“…These included variants in ACTG1, CDH23, COCH, COL4A5, COL11A2, CRYM, EYA1, GJB2, GJB3, GJB6, KCNQ4, LOXHD1, MARVELD2, MYH9, MYO6, MYO7A, MYO15A, OTOF, SIX1, SLC26A4, TECTA, TMC1, TMIE, TMPRSS3, USH1C, USH2A , and WFS1 . Their list of new candidate variants, which is being published separately, attests to the requirement for ethnic-specific data and includes variants in ACTG1, COCH, COL11A2, GRXCR1, KCNQ4, MYO6, MYO15A , and TMPRSS3 [3642]. …”
Section: Diagnostic Ratementioning
confidence: 99%
“…With regard to the effectiveness of CI, Nagy et al reported that CI had no benefit in patients with COCH mutations (Nagy et al, ), while other reports, including our own, have described improved results after CI (Street et al, ; Vermeire et al, ; Tsukada et al, ). A previous temporal bone study reported that spiral ganglions were able to survive even though there was extensive degradation of cochlear dendrites (Khetarpal et al, ), indicating that the remaining spiral ganglion cells can be stimulated by CI, resulting in an improved performance after CI in patients with COCH mutations.…”
Section: In Patients With Specific Genetic Backgroundsmentioning
confidence: 63%
“…The proband was a 70‐year‐old man (III‐2) (Fig. ) (Tsukada et al, ). In his early 50s he experienced hearing loss for the first time, which was not accompanied with tinnitus or vertigo.…”
Section: In Patients With Specific Genetic Backgroundsmentioning
confidence: 99%